Is the USA set to dominate accreditation of engineering education and professional qualifications? - Anwar, Arif A.; Richards, D. (Thomas Telford Ltd., 2013)
This paper examines mutual recognition of professional engineering qualifications and the globalisation of accreditation of engineering education by US organisation ABET. Scrutiny of the Washington Accord on mutual recognition and a recent attempt to gain ABET accreditation for a UK civil engineering degree programme highlights differences between ABET and the UK Engineering Council. The ambiguity of the Washington Accord also means it may be interpreted differently by signatories. It is suggested that ABET accreditation and the US professional engineer (PE) qualification may become the de-facto global standard due to lack of significant competition from the UK or Europe.